Agriculture negotiations priorities and sustainable development at the WTO - Calvo, Facundo (International Food Policy Research Institute, 2024)
During a meeting of the WTO Committee on Agriculture in Special Session (CoASS) in June 2023, agricultural negotiators made new submissions on domestic support and export restrictions. Submissions on domestic support were made by the African Group, the Cairns Group -a coalition of developed and developing agricultural exporting economies-, and Costa Rica. The United Kingdom also submitted an analytical paper on export restrictions, making the case for WTO members to pursue more focused discussions on the food security impact of export restrictions on agricultural products, based on data and members’ experiences.